Stabilization of magnetite nano iron oxide with a series of novel surfactants - Chin, Swee Yee; Chan, Samuel Hong Shen; Wan Zurina, Samad; Dipsikha; Panchanan, Pramanik; Nik Idris; Jumat, Salimon; Ambar, Yarmo (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia